ADOLESCENTS AND ONLINE GAMBLING: RISK FACTORS, ACCESS RESTRICTIONS MEASURES AND PROTECTIVE MECHANISMS IN KAZAKHSTAN (Journal of actual problems of jurisprudence, 2026)
The digitalization of gambling and the rapid expansion of online betting services and mobile applications increase the risk of minors’ involvement in online gambling, making this phenomenon a pressing issue for legal regulation and public safety. The findings indicate that Kazakhstan has established a basic legal framework for the gambling sector and applies monitoring and blocking mechanisms against the illegal online segment; however, the cross-border nature of the online environment, fast payments, anonymity, mirror sites, and technical circumvention tools limit the long-term effectiveness of these measures. Key vulnerabilities include insufficient standardization of age verification (age verification/KYC) and the growing impact of digital marketing in the new media ecosystem (embedded social media advertising, influencer integrations, sports-content-linked promotions, and bonus/offer mechanics).The aim of this study is to analyze the legal mechanisms in force in Kazakhstan to protect minors from online gambling, assess the effectiveness and vulnerabilities of access-restriction and preventive measures, and develop evidence-based conclusions for improving regulation through a comparative review of foreign and CIS practices.The study employs formal-legal, systemic, and comparative legal methods, complemented by an analysis of law-enforcement practice based on official publications of authorized bodies.The scientific and practicalsignificance of the article is determined by the factthat the problem of protection of minors is considerednotonlyas a moral and socialproblem,butalsoas a problem of legalsecurityandregulatoryeffectivenessin the digitalage.This research is funded by the Committee of Science of the Ministry of Science and Higher Education of the Republic of Kazakhstan within the framework of the program «Integrative Study of Gambling Addiction in Kazakhstan and Multidisciplinary Strategies for Its Minimization»  (Grant № BR24992927).Keywords: adolescents, online gambling, gambling disorder, access restriction, age verification, legal regulation, advertising, prevention.